ETFAD/EADV Eczema task force 2015 position paper on diagnosis and treatment of atopic dermatitis in adult and paediatric patients. (23rd March 2016) - Wollenberg, A.; Oranje, A.; Deleuran, M.; Simon, D.; Szalai, Z.; Kunz, B.; Svensson, A.; Barbarot, S.; von Kobyletzki, L.; Taieb, A.; de Bruin‐Weller, M.; Werfel, T.; et al.
Abstract: Atopic dermatitis (AD) is a clinically defined, highly pruritic, chronic inflammatory skin disease of children and adults. The diagnosis is made using evaluated clinical criteria. Disease activity is best measured with a composite score assessing both objective signs and subjective symptoms, such as SCORAD. The management of AD must consider the clinical and pathogenic variabilities of the disease and also target flare prevention. Basic therapy includes hydrating topical treatment, as well as avoidance of specific and unspecific provocation factors. Anti‐inflammatory treatment of visible skin lesions is based on topical glucocorticosteroids and the topical calcineurin inhibitors tacrolimus and pimecrolimus. Topical calcineurin inhibitors are preferred in sensitive locations. Tacrolimus and mid‐potent steroids are proven for proactive therapy, which is long‐term intermittent anti‐inflammatory therapy of the frequently relapsing skin areas. Systemic anti‐inflammatory or immunosuppressive treatment is indicated for severe refractory cases. Biologicals targeting key mechanisms of the atopic immune response are promising emerging treatment options. Microbial colonization and superinfection may induce disease exacerbation and can justify additional antimicrobial treatment. Systemic antihistamines (H1R‐blockers) may diminish pruritus, but do not have sufficient effect on lesions. Adjuvant therapy includes UV irradiation, preferably UVA1 or narrow‐band UVB 311 nm. Dietary recommendations should be patient specific and elimination diets should only be advised in case of proven food allergy. Allergen‐specific immunotherapy to aeroallergens may be useful in selected cases. Psychosomatic counselling is recommended to address stress‐induced exacerbations. 'Eczema school' educational programmes have been proven to be helpful for children and adults.